Retrospective investigation of the origin and epidemiology of the dengue outbreak in Yunnan, China from 2017 to 2018 - Cao, Liang; Yu, Ziping; He, Haiqiang; Guo, Xiaofang; Wei, Chun; Zhang, Xuancheng; Bao, Junduo; Li, Chenghui; Zhou, Hongning; Xin, Jialiang; Nan, Fulong (Frontiers in Veterinary Science, 2023)
Since 2013, a dengue epidemic broke out in Yunnan, China and neighboring countries. However, after the COVID-19 pandemic in 2019, the number of dengue cases decreased significantly. In this retrospective study, epidemiological and genetic diversity characterizations of dengue viruses (DENV) isolated in Yunnan between 2017 and 2018 were performed. The results showed that the dengue outbreak in Yunnan from 2017 to 2018 was mainly caused by DENV1 (genotype I and genotype V) and DENV2 (Asia I, Asia II, and Cosmopolitan). Furthermore, correlation analysis indicated that there was a significant positive correlation between the number of imported and local cases (correlation coefficient = 0.936). Multiple sequence alignment and the phylogenetic divergence analysis revealed that the local isolates are closely related to the isolates from Myanmar and Laos. Interestingly, recombination analysis found that the DENV1 and DENV2 isolates in this study had widespread intra-serotype recombination. Taken together, the results of the epidemiological investigation imply that the dengue outbreak in Yunnan was mainly caused by imported cases. This study provides a new reference for further investigations on the prevalence and molecular epidemiology of DENV in Yunnan, China.